IMPROVING STUDENT’S MATHEMATICAL REASONING AND SELF CONCEPT BY USING RECIPROCAL TEACHING - Dani Agung Prasetio; Utari Sumarmo; Asep Ikin Sugandi (IKIP Siliwangi, 2018)
This study is a pretest-postest experiment control group design having a goal to analyze the role of Previous Mathematical Ability and Reciprocal Teaching in mathematics (RTM) on students’ mathematical reasoning ability (MRA) and self concept in mathematics (SCM). The study involves 66 seventh grade students, a PMA test, a MRA test, and a SCM scale, and student’s perception on RTM. The study revealed that RTM took better role than PMA on obtaining MRA and SCM. For entirely students and of students with high PMA in both teaching approaches and the grades of MRA and SCM were at high level. Besides that, study found there were no association between MRA and SCM and there were no interaction between PMA and teaching approaches toward RMA and SCM. Like that, students expressed positive opinion on RTM, even if, student still realized few difficulties in solving MRA,